POLA KEPEMIMPINAN PESANTREN DALAM PEMBENTUKAN KARAKTER ISLAMI DAN KESIAPAN GLOBAL SANTRI: STUDI KASUS PONDOK PESANTREN NAHDLATUTH THULLAB - Afida Naili Urnika; Siti Aimah (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze Islamic boarding school leadership patterns in shaping Islamic character and global readiness among students at the Nahdlatuth Thulab Islamic Boarding School. The study employed a qualitative approach with a case study design. Data were obtained through in-depth interviews, non-participant observation, and documentation studies involving boarding school administrators, teaching staff, administrative staff, and senior students. Data analysis was conducted using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and drawing and verifying conclusions. The research results indicate that the leadership style at the Nahdlatuth Thulab Islamic Boarding School is integrative, combining religious values ​​with a structured institutional system. This leadership style plays an effective role in shaping the Islamic character of students through the instilling of faith, piety, noble morals, discipline, and responsibility. Furthermore, the leadership of the Islamic boarding school also contributes to preparing students for global readiness by strengthening their learning ethos, independence, adaptability, and educational management that is responsive to current developments without losing the Islamic boarding school's identity. This research concludes that the leadership style of the Islamic boarding school plays a strategic role as a bridge between tradition and modernity, enabling the boarding school to produce students with Islamic character and global competitiveness